ANALISIS DAN PEMETAAN DAERAH KRITIS RAWAN BENCANA WILAYAH UPTD SDA TUREN KABUPATEN MALANG - Galih Damar Pandulu (Universitas Tribhuwana Tunggadewi Malang, 2016)
Disasters in the area of Technical Implementation Unit Office of Turen, especially those caused by water damage requires the prevention and treatment of good and effective. In an effort to manage critical areas and disaster-prone river in the region, especially in the working area, in need of maps and data critical areas and prone to such disasters. The expected result is the availability of critical distribution maps and disaster-prone areas related to water resources in the area of Regional Technical Implementation Unit Turen Malang. The analytical methods used are scoring Analysis disaster-prone areas and analysis of the level of vulnerability and the risk of flooding. Results of research on critical land get there in the districts and sub-districts Poncokusumo Wajak, while the level of vulnerability to flooding obtain flood prone land area of 137.36 km2 and is very prone to flood an area of 3:35 km2.